EFEK KONTAGION KRISIS DUBAI TERHADAP RETURN SAHAM DI NEGARA-NEGARA ASIA TENGGARA - Solechuddin .; D. Agus Harjito (Jurnal Ekonomi dan Bisnis, 2011)
Dubai Crisis has shocked global stock exchange indicated by the downward of stock exchange index at stock markets in Europe and Asia. This study investigates to review the effect of Dubai Crisis toward stock return in ASEAN countries i.e. Indonesia, Singapore, Malaysia, Thailand and Philippine (contagion theory). Data used in this study is stock prices two months before and after Dubai stated that its government was in default or failure to payon November 28, 2009. This study used regression to analyze the effect of Dubai Crisis as origin country to affective countries. Result of the analysis showed that the Dubai Crisis was significantly affected the stock price of Malaysia on the third day with the significance level 10%. Malaysia’s stock price significantly affected the stock price of Singapore on the third day at significance level 1%. It also significantly affected the stock price of Thailand on the first day at significance level 10%.Keyword: Dubai crisis, contagion effect, stock return, ASEAN countries.